1972
DOI: 10.1139/g72-018
|View full text |Cite
|
Sign up to set email alerts
|

CYTOLOGICAL EFFECTS OF THE PESTICIDES PHOSDRIN AND BLADEX ON TRADESCANTIA AND VICIA FABA

Abstract: The cytological effects of the insecticide Phosdrin (mevinphos) and the herbicide Bladex on root tips of Tradescantia and Vicia faba were observed and compared with those of the chemical mutagen ethyl methane sulfonate (EMS). In addition, plants of Vicia faba were sprayed prior to floral initiation and pollen mother cells examined for chromosomal abnormalities. Phosdrin and Bladex produced the same kinds of chromosome abnormalities as EMS, namely, fragments, bridges, multipolar anaphases and lagging chromosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
2

Year Published

1981
1981
1993
1993

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 11 publications
2
19
0
2
Order By: Relevance
“…Such differences in the effectiveness of a chemical may be due to the differences in the deactivating/activating enzymes present in plants or mam The comparison of the actual aberrations as well as radiomimetic effectiveness revealed that Allium system is more sensitive than Hordeum. Such differences in toxicities were earlier observed in V. faba and Tradescantia following treatments with phosdrin and bladex (Ahmed and Grant 1972). Sparrow and Evans (1961) found a high correlation of nuclear volume and nuclear DNA content with radiosensitivity in higher plants thus indicating that cells of one plant system may be more radiosensitive as compared to the other.…”
Section: Discussionsupporting
confidence: 55%
“…Such differences in the effectiveness of a chemical may be due to the differences in the deactivating/activating enzymes present in plants or mam The comparison of the actual aberrations as well as radiomimetic effectiveness revealed that Allium system is more sensitive than Hordeum. Such differences in toxicities were earlier observed in V. faba and Tradescantia following treatments with phosdrin and bladex (Ahmed and Grant 1972). Sparrow and Evans (1961) found a high correlation of nuclear volume and nuclear DNA content with radiosensitivity in higher plants thus indicating that cells of one plant system may be more radiosensitive as compared to the other.…”
Section: Discussionsupporting
confidence: 55%
“…This might indicate that maize is relatively less sensitive to chromosome breaks with the used IGRs. Differences between plants species in chromosome sensitivity to chemically induced breaks were reported by Ahmed and Grant (1972). Most of the observed bridges in the present work were sticky bridges which might be formed due to stickiness.…”
Section: The Effect Of Igrs On Meiotic Behaviourssupporting
confidence: 53%
“…g. Reddy and Rao 1969, Ahmed and Grant 1972, Amer and Ali 1974, Amer and Farah 1976, Reddy and Rao 1981and Badr et al 1986). …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Ahmed and Grant (1972) noticed in Tradescantia, the occurrence of lower rates of breaks than in V. faba after treatments with phosdrin, bladex and the well known mutagen EMS. They concluded that chemically induced breaks depends on the sensitivity of the chromosomes of the plant species.…”
mentioning
confidence: 65%
“…Such types of irregularities were also found after treatments with different pesticides (Ahmed and Grant 1972, Tomkins and Grant 1972, Pusztai and Vegh 1978, Allam et al 1980and Elnadi et al 1983). The most frequent types of mitoclassic effect which observed after different treatments with XRD 473 and IKI 7899 were abnormal metaphases and anaphases due to stickiness (Plate 1-2 and plate 11-2, 3) as well as lagging chromosomes (Plate I-5 and plate 11-6).…”
mentioning
confidence: 76%